2008
DOI: 10.1016/j.cell.2008.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Induced Pluripotent Stem Cells

Abstract: Tissue culture of immortal cell strains from diseased patients is an invaluable resource for medical research, but is largely limited to tumor cell lines or transformed derivatives of native tissues. Here we describe the generation of induced pluripotent stem (iPS) cells from patients with a variety of genetic diseases with either Mendelian or complex inheritance that include: adenosine deaminase deficiency-related severe combined immunodeficiency (ADA-SCID), Shwachman-Bodian-Diamond syndrome (SBDS), Gaucher d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,550
1
28

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,025 publications
(1,590 citation statements)
references
References 32 publications
11
1,550
1
28
Order By: Relevance
“…Cellular models built on patient-specific iPS cells have successfully shown disease phenotypes, also when modeling psychiatric disorders (Christian et al, 2012;Park et al, 2008). The few reprogramming studies of cells from patients with psychiatric disorders have had encouraging results, proving the principle, as well as presenting possible molecular mechanisms.…”
Section: Analysesmentioning
confidence: 99%
“…Cellular models built on patient-specific iPS cells have successfully shown disease phenotypes, also when modeling psychiatric disorders (Christian et al, 2012;Park et al, 2008). The few reprogramming studies of cells from patients with psychiatric disorders have had encouraging results, proving the principle, as well as presenting possible molecular mechanisms.…”
Section: Analysesmentioning
confidence: 99%
“…Disease modeling based on ESC culture is also limited for the same reason (Yamashita et al, 2006;Schneider et al, 2007;Crews et al, 2008). Strikingly, since Yamanaka's and Thomson's exciting experiments on iPSCs in 2007 (Takahashi et al, 2007;Yu et al, 2007), the successful reprogramming of fibroblasts has been accomplished for a variety of neurodegenerative and neurodevelopmental diseases, such as amyotrophic lateral sclerosis (ALS), PD (Dimos et al, 2008;Park et al, 2008;Soldner et al, 2009) Lee et al, 2009), and AD (Israel et al, 2012). The reprogramming of patient fibroblasts to human iPSCs, followed by iPSC differentiation into neurons, produces a near limitless source of live human neurons that are genetically identical to those present in patients, with which the disorder can be extensively studied.…”
Section: Modeling Of Neuronal Disorders With Nscsmentioning
confidence: 99%
“…The pathogenesis of PD is caused by the accumulation of misfolded alpha-synuclein into the intracellular Lewy bodies (Aarsland et al, 2009;Schulz-Schaeffer, 2010;Vekrellis et al, 2011) and insufficient dopamine expression in neurons in the substantia nigra of the midbrain (Goedert, 2001;Braak et al, 2007). Fibroblasts from PD patients have been successfully reprogrammed and differentiated into dopamine neurons (Park et al, 2008;Soldner et al, 2009). Strikingly, Wernig et al (2008 demonstrated that transplantation of mouse iPSC-differentiated dopamine neurons could be functionally integrated into the midbrain of PD rats.…”
Section: Modeling Of Neuronal Disorders With Nscsmentioning
confidence: 99%
“…65,66 In the recent past, also a variety of iPS lines from single-gene disorders, chromosome syndromes and complex diseases have been generated and it would be of great interest to use iPS lines from infertile men as in vitro models for germ cell formation. 67,68 However, the spectrum of usable ES cells with an inherited defect is limited, because in vitro fertilisation with preimplantation genetic diagnosis is only rarely applied. And whereas the usage of iPS cells derived from adults has the advantage that the detailed clinical history of the patient is known, one must take into account that such cells might have already accumulated other mutations, which might then interfere with the in vitro studies on spermatogenesis.…”
Section: Amniotic Fluid Stem (Afs) Cells Could Be a Useful Tool To Stmentioning
confidence: 99%